The significance of Jesus' utterance in relation to the Johannine Son of Man: a speech act analysis of John 9:35 - H. Ito (Acta Theologica)
The purpose of my previous article was to continue to show the validity of a speech act approach and to develop it further in the reading of biblical texts. As a successive study, this article aims to present yet another speech act analysis, which will put more focus on a demonstration that this approach is able to deal even with more difficult exegetical and interpretational issues in the text adequately on its own terms. In order to accomplish that, this article will examine the significance of Jesus’ utterance in John 9:35, which contains some difficulty in interpreting the meaning of the title Son of Man.